2018
DOI: 10.1108/pr-11-2016-0306
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype threat and older worker’s attitudes: a mediation model

Abstract: Purpose-Taking a social identity approach, the purpose of this paper is to examine the extent to which age-based stereotype threat mediates the relationships between older workers' negative age-based metastereotypes and two negative work attitudes: organizational disidentification and work disengagement. Design/methodology/approach-A two-wave cross-sectional design was adopted to collect data from 423 blue-collar older workers of the Portuguese manufacturing sector. Structural equation modeling was used to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
(157 reference statements)
0
11
0
Order By: Relevance
“…First, affective commitment, or its absence, can explain employees' diminished efforts to help their colleagues in the presence of heavily politicized organizational climates. Other factors could explain this connection too, such as employees' beliefs about organizational unfairness (Liu and Berry, 2013), person–organization misfit (Boon and Biron, 2016) or work disengagement (Oliveira and Cabral Cardoso, 2018). In a related sense, we propose several reasons employees might grow less affectively committed to their organization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…First, affective commitment, or its absence, can explain employees' diminished efforts to help their colleagues in the presence of heavily politicized organizational climates. Other factors could explain this connection too, such as employees' beliefs about organizational unfairness (Liu and Berry, 2013), person–organization misfit (Boon and Biron, 2016) or work disengagement (Oliveira and Cabral Cardoso, 2018). In a related sense, we propose several reasons employees might grow less affectively committed to their organization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These measures were included within these studies to confirm the existence of ABST and link it to any resulting performance deficits. Other research has similarly used self-reporting to examine perceived stereotype threat within the workplace ( Kulik et al, 2016 ; Phibbs and Hooker, 2017 ; Oliveira and Cabral-Cardoso, 2018 ; Manzi et al, 2019 ; von Hippel et al, 2019 ). These studies tend to measure the perceived experience of threat—e.g.…”
Section: Studymentioning
confidence: 99%
“…Beyond ‘performance’ outcomes, a documented consequence of stereotype threat is described as ‘disidentification’ or ‘disengagement’, characterized by lower intentions to engage in a stereotyped task/domain ( Davies et al, 2005 ). Indicative of disidentification, a growing body of research has shown that ‘older’ or ‘mature’ workers (usually categorized as aged 45/50+ and mean age of mid-50s) who perceive more negative age-based stereotyping in the workplace are also more likely to hold negative work attitudes and show greater disengagement with their work ( Kulik et al, 2016 ; Oliveira and Cabral-Cardoso, 2018 ; Manzi et al, 2019 ; von Hippel et al, 2019 ). In addition, one study found that making age stereotypes salient reduced older people’s subjective assessment of their own hearing ability ( Barber and Lee, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a fairly novel concept in the research of alarming workplace behaviors, workplace ostracism is passive aggression which may refer to giving the silent treatment to particular individuals. While the repercussions of ostracism have been studied by a tenfold to underline its alarming psychological distress and workplace deviance (Robinson et al, 2013;Oliveira & Cardoso, 2018), the facets against which this concept has been tested against are quite limited.…”
Section: Workplace Ostracismmentioning
confidence: 99%
“…d Generational diversity, as a constituent of various cohorts, has also been an abode for unspoken subjective norms indulged on its cohorts, as evidenced by the Social Identity Theory's social self (Oliveira & Cardoso, 2018). This is extrapolated by the congruence of the part of an individual an employee in this scenario which is a reflection of his or her membership in a social group age cohorts in this situation which they work to salvage (Tajfel, 1982).…”
Section: Generational Diversity and Workplace Ostracismmentioning
confidence: 99%